Mucinous cystic neoplasm of the liver: a case report and review of the literature - Bravo-Taxa, Mercedes (2021)
Mucinous cystic neoplasm (MCN) of the liver is an unusual cyst-forming epithelial neoplasm, typically showing no communication with the bile ducts. This neoplasm represents less than 5% of all cystic lesions of the liver and there are only 250 cases in the world literature. We present the case of a 23-year-old female with a 13.5 x 10.2 cm lesion, hypodense, lobulated, with multiple septa up to 2.5 mm thick and small cystic images inside, which produces intrahepatic bile duct and common bile duct dilatation. The pathological study concluded that the tumor corresponded to a mucinous cystic neoplasm of the liver.